The Influence of Digital Marketing Strategy, Brand Image and Sales Performance with Customer Loyalty as a Moderating Variable - Nanik Istianingsih; Ariyanto M (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of e-commerce has transformed retail landscapes worldwide, reshaping consumer behavior and intensifying market competition. In Indonesia, Shopee has emerged as a dominant platform in the online fashion sector, leveraging digital marketing strategies, brand image, and customer loyalty to drive sales performance. This study aims to know the effect of digital marketing strategies, brand image on sales performance of Muslim fashion moderated with customer loyalty on Shopee Indonesia. This study used a quantitative approach and employs analysis techniques using SEM-PLS with 213 respondents of Shopee customers. The study showed digital marketing strategies, brand image, and sales performance has significant and positive relationship between. The relationship between marketing strategies and customer loyalty, either directly or as a moderation on sales performance, has not had a significant effect. This research offers important perspectives for e-commerce aiming to enhance their marketing approaches and overall sales in the ever-evolving online Muslim fashion retail sector.